Estimating the economic impact of a port through regional input–output tables: Case study of the Port of Cartagena (Spain). Issue 4 (December 2016) - Artal-Tur, Andrés; Gómez-Fuster, José María; Navarro-Azorín, José Miguel; Ramos-Parreño, José María
Abstract In this article we estimate the economic impact of the Port of Cartagena on the economy of the Region of Murcia by using a regional input–output table, and by separating port activity related to freight traffic from that linked to passengers (cruises). In 2011, the Port of Cartagena generated an activity estimated at about 3.81 per cent of regional GVA, and 2.11 per cent of regional employment. In relation to 2000, these figures represent an increase of 1.1 per cent in GVA and 0.1 per cent in employment. Compared with the large economic impact of freight-related activities, the impact of cruise tourism expenditure is relatively low, suggesting the need of new business lines to be taken into account. Investments on cruise docks and terminals, or the possibility of transforming Cartagena into a home port might be a good chance to attract more cruise passengers and increase economic impact of the cruise industry.